-2x-(x-2)=5x+3(x+1)

Simple and best practice solution for -2x-(x-2)=5x+3(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-(x-2)=5x+3(x+1) equation:


Simplifying
-2x + -1(x + -2) = 5x + 3(x + 1)

Reorder the terms:
-2x + -1(-2 + x) = 5x + 3(x + 1)
-2x + (-2 * -1 + x * -1) = 5x + 3(x + 1)
-2x + (2 + -1x) = 5x + 3(x + 1)

Reorder the terms:
2 + -2x + -1x = 5x + 3(x + 1)

Combine like terms: -2x + -1x = -3x
2 + -3x = 5x + 3(x + 1)

Reorder the terms:
2 + -3x = 5x + 3(1 + x)
2 + -3x = 5x + (1 * 3 + x * 3)
2 + -3x = 5x + (3 + 3x)

Reorder the terms:
2 + -3x = 3 + 5x + 3x

Combine like terms: 5x + 3x = 8x
2 + -3x = 3 + 8x

Solving
2 + -3x = 3 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
2 + -3x + -8x = 3 + 8x + -8x

Combine like terms: -3x + -8x = -11x
2 + -11x = 3 + 8x + -8x

Combine like terms: 8x + -8x = 0
2 + -11x = 3 + 0
2 + -11x = 3

Add '-2' to each side of the equation.
2 + -2 + -11x = 3 + -2

Combine like terms: 2 + -2 = 0
0 + -11x = 3 + -2
-11x = 3 + -2

Combine like terms: 3 + -2 = 1
-11x = 1

Divide each side by '-11'.
x = -0.09090909091

Simplifying
x = -0.09090909091

See similar equations:

| -9+8s=8s-2 | | 3(2x+y)= | | duck+duck=wink | | 65y=32(2y+11) | | 13(x-3)=-6-7 | | .40+.70(100)=.60(100+x) | | 220x-x^2=0 | | 5(y-2)= | | 8/3=h/15 | | x+2=3-4 | | 2x+17=4x-13 | | 3g-3= | | -15x^2+1050x-9000=0 | | D-th=u | | 4t=-t+5t | | 5m(2m+3)= | | x^3y-3x^2y^2-40xy^3=0 | | x^8=656 | | y-x=0 | | 5y+8=20x+43 | | 0.9x-5.6=0.7 | | 12g-7=5 | | (x)(x)-2x-15=0 | | -4(t-3)+7t=8t-2 | | 5(5x-5)+3=25x-22 | | 3/8-m/9=7/72 | | -4x+3y+1=0 | | 2x+30=140 | | 3(5c-1)(-2)=13c+3 | | 2x+80=140 | | 8x+2=8(x-8) | | -2x-3-5x=2(x-1) |

Equations solver categories